2008
DOI: 10.47102/annals-acadmedsg.v37n1p63
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Lesions of the Talus

Abstract: Osteochondral lesions of the talus can present as a late complication of ankle injuries. As the talus is largely covered by articular cartilage, it has a limited ability for repair. Early and accurate diagnosis is important as talar integrity is required for optimal function of the ankle. The common presentation is chronic ankle pain with a history of ankle trauma. Conservative treatment involving a period of casting and non-weight-bearing is recommended for acute, non-displaced osteochondral lesions. Surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Diameter of the lesions usually did not exceed 1.5 cm. A total of 18 studies, including 388 patients, described the results of BMS [2, 3, 5, 8, 11, 13, 14, 17–19, 21, 34, 36, 37, 48, 52, 55, 60]. In 329 of 386 patients, treatment was reported to be successful (85%).…”
Section: Resultsmentioning
confidence: 99%
“…Diameter of the lesions usually did not exceed 1.5 cm. A total of 18 studies, including 388 patients, described the results of BMS [2, 3, 5, 8, 11, 13, 14, 17–19, 21, 34, 36, 37, 48, 52, 55, 60]. In 329 of 386 patients, treatment was reported to be successful (85%).…”
Section: Resultsmentioning
confidence: 99%
“…Although recent studies confirmed a roughly 45% success rate for non-operative management, there is still controversy whether this approach leads to arthritis or not. 15 Surgical treatment of OLTs can be performed either through open or arthroscopic techniques. The aim is to stimulate the healing process of the defected cartilage, which can be achieved either by micro fracturing or grafting hyaline cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Ogilvie-Harris scoring system, which consists of swelling, stiffness, pain measurement, and activity, was used. The results were ranked as excellent (15-16 points), good, 15,16 or poor (< 13).…”
Section: Follow-up Evaluationsmentioning
confidence: 99%
“…Arthroscopically assisted approaches have been used by many authors for the treatment for cartilage defects of the talar dome [3, 7, 17, 18, 20]. The main difficulty reported with this technique concerns the accessibility of the posteromedial and central regions of the talar articular surface, often requiring an additional osteotomy of the medial malleolus [6, 26] or a transmalleolar approach [19, 27, 31].…”
Section: Introductionmentioning
confidence: 99%